KALIMAT EFEKTIF DALAM KOMUNIKASI DAN PENULISAN ILMIAH - Ameilia; Bagas Teguh Wijaya; Dimas Abi Pratama; Ira Yuniati; Lezita Malianti (STKIP Subang, 2026)
The widespread use of wordy, ambiguous, and illogical sentences in daily communication and academic writing often leads to misunderstandings and reduces the efficiency of message delivery. This study aims to analyze the concepts, main characteristics, core requirements, functions, and practical applications of effective sentences across various communication contexts. Utilizing a non-field qualitative design with a content analysis-based descriptive approach, data were gathered through a literature study comprising primary theoretical grammar resources and secondary academic references. The data collection technique employed documentation, critical reading, and note-taking to categorize ineffective sentence structures and their corrected forms. Data analysis followed an interactive qualitative model involving data reduction, systematic presentation, and conclusion drawing. The findings reveal that sentence effectiveness relies on five key criteria: unity of thought, coherence, precise diction, word economy, and logical structure. Structural mismatch due to misplaced prepositions, wordiness (e.g., double plurals), synonymous adverbs, and excessive conjunctions are identified as the most frequent errors in written and oral discourse. Eliminating redundant function words and restoring clear subject-predicate relations significantly enhance text clarity and readability. In conclusion, mastering and consistently implementing effective sentence principles are essential skills for achieving concise, logical, and professional communication in academic and everyday settings.